Athletic pubalgia (sports hernia) - Litwin, D. E. M.; Sneider, E. B.; McEnaney, P. M.; Busconi, B. D. (Clinics in Sports Medicine, 2011)
Athletic pubalgia or sports hernia is a syndrome of chronic lower abdomen and groin pain that may occur in athletes and nonathletes. Because the differential diagnosis of chronic lower abdomen and groin pain is so broad, only a small number of patients with chronic lower abdomen and groin pain fulfill the diagnostic criteria of athletic pubalgia (sports hernia). The literature published to date regarding the cause, pathogenesis, diagnosis, and treatment of sports hernias is confusing. This article summarizes the current information and our present approach to this chronic lower abdomen and groin pain syndrome.